The Malandreo and the reproduction of violence in Venezuela // El Malandreo y la reproducción de la violencia en Venezuela - Vandenbogaerde, Ellen (Espacio Abierto, 2019)
AbstractThis article explores the meaning and expressions of ‘el malandreo’, a Venezuelan gangster identity, with particular attention for the deadly violence it applies. Much of the deadly violence in Venezuela is attributable to malandros, people that identify with el malandreo, but relatively little research has evaluated this type of violence or its presumed protagonists in this context. Based on primary qualitative data gathered in two different cities, this article develops an understanding of el malandreo as an institution, that is, as a social structure that proscribes and encourages certain behaviours, in this case violent behaviours. Malandros, Venezuelan slang for delinquents of various trades and assignations tend to associate in relatively disorganised groups more or less embedded in the barrio. This article argues that what weaves these varying shapes and forms together is a conflictive network of fear and lethal reprisal. El malandreo has found a substantial following in Venezuela’s barrios, providing predominantly young boys growing up among informality and relative insecurity with existential meaning and respect. What sustains and further legitimises this institution today, over and above poor living conditions, is its deadly, reciprocal violence. The malandro claims to protect the barrio from random violence, through what he considers to be legitimate violence, generating cycles of retaliatory violence. The ‘culebra’, a Venezuelan colloquialism for retaliatory violence, thus has important endogenous feedback effects, sowing the conditions for future violence and simultaneously sustaining el malandreo as a legitimate governance structure.ResumenEste artículo explora el significado y las expresiones del ‘malandreo’, una identidad gánster venezolana, con particular atención en la violenciamortalqueaplica. A pesar de que gran parte de la violencia mortal en Venezuela es atribuible a malandros, personas que se identifican con el ‘malandreo’, relativamente pocas investigaciones han evaluado este tipo de violencia o sus presuntos protagonistas en este contexto. Basado en un trabajo de investigación cualitativo en dos ciudades diferentes, este artículo desarrolla una comprensión del malandreo como una institución, es decir, como una estructura social que proscribe y fomenta ciertas conductas, en este caso, violentas. Los malandros, jerga venezolana para delincuentes de diversos oficios y asignaciones, tienden a asociarse a grupos relativamente desorganizados, más o menos integrados en sus barrios. Este artículo argumenta que lo que entrelaza estas formas variadas es una red conflictiva de miedo y represalias letales. El ‘malandreo’ ha atraído un número considerable de seguidores en los barrios de Venezuela, proporcionando respeto y un significado existencial a varones jóvenes, creciéndose en ambientes informales y relativamente inseguros. Lo que sostiene y legitima a esta institución el día de hoy, más allá de precarias condiciones de vida, es su violencia recíproca y letal. El malandro pretende proteger al barrio de una violencia gratuita, a través de lo que considera una violencia legítima, generando ciclos de violencia vengativa. La ‘culebra’, un coloquialismo venezolano para la violencia reciproca, tiene importantes efectos endógenos, sembrando las condiciones para nuevos episodios de violencia y, al mismo, tiempo sosteniendo al ‘malandreo’ como una estructura de gestión social legítima.